Deciphering Ageing Effects in Green-Dyed English Wool Carpet Yarns from the 1840s - Terry T. Schaeffer; Jacob Mobberley; Laura Maccarelli (Heritage, 2025)
In 1842, carpet manufacturer W.H. Worth of Kidderminster, England, began assembling a sample book of wool yarns dyed with natural dyestuffs. This paper reports on a study of the “Greens” section, which contains sixteen yarn samples—six still green and ten now ranging from tan to dark brown. The accompanying recipes list similar ingredients: old fustic and either “mixture” or extracet of indigo. To verify whether Worth’s recipes were followed, the yarns were analyzed using HPLC-DAD and FORS. Additionally, mock-ups were prepared according to Worth’s green dye recipes and subjected to thermal ageing to explore potential causes of discoloration. Preliminary analysis of the historic samples revealed that the discoloured yarns contain both indigo and indigo carmine, while the still-green samples contain only indigo carmine. This suggests that one or more components of the indigo vat may have contributed to discoloration. To test this hypothesis, contemporary wool yarns were dyed using a Worth green recipe, with and without indigo, at varying pH levels. These were thermally aged, and their colour changes monitored. HPLC-DAD and FORS analyses of the mock-ups were compared to the historic samples to identify dyeing conditions that may have led to the observed browning.